Relationship Between QT Interval and Outcome in Low‐Flow Low‐Gradient Aortic Stenosis With Low Left Ventricular Ejection Fraction - Abdellaziz Dahou; Oumhani Toubal; Marie‐Annick Clavel; Jonathan Beaudoin; Julien Magne; Patrick Mathieu; François Philippon; Jean G. Dumesnil; Rishi Puri; Henrique B. Ribeiro; Éric Larose; Josep Rodés‐Cabau; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundQT interval has been shown to be associated with cardiovascular events. There is no data regarding the association between QT interval and left ventricular (LV) function and prognosis in patients with low LV ejection fraction (LVEF), low‐flow, low‐gradient aortic stenosis (LF‐LG AS). We aimed to examine the relationship between corrected QT interval (QTc) and LV function and outcome in these patients. Methods and ResultsNinety‐three patients (73±10 years; 74% men) with LF‐LG AS (mean gradient <40 mm Hg and indexed aortic valve area ≤0.6 cm2/m2) and reduced LVEF (≤40%) were prospectively included in this analysis and 63 of them underwent aortic valve replacement within 3 months following inclusion. Prolonged QTc was defined as QTc >450 ms in men and >470 ms in women. LV global longitudinal strain was measured by speckle tracking and expressed in absolute value |%|. QTc correlated with the following: global longitudinal strain (r=−0.40, P=0.005), LVEF (r=−0.27, P=0.02), stroke volume (r=−0.35, P=0.007), and B‐type natriuretic peptide (r=0.45, P=0.0006). During a median follow‐up of 2.0 years, 49 patients died. Prolonged QTc was associated with a 2‐fold increase in all‐cause mortality (hazard ratio=2.05; P=0.01) and cardiovascular mortality (hazard ratio=1.89; P=0.04). In multivariable analysis adjusted for EuroSCORE, aortic valve replacement, previous myocardial infarction, LVEF, and ß‐blocker medication, prolonged QTc was independently associated with all‐cause mortality (hazard ratio=2.56; P=0.008) and cardiovascular mortality (hazard ratio=2.50; P=0.02). ConclusionsIn patients with LF‐LG AS and reduced LVEF, longer QTc interval was associated with worse LV function and increased risk of death. Assessment of QTc may provide a simple and inexpensive tool to enhance risk stratification in LF‐LG AS patients. Clinical Trial RegistrationURL: https://www.clinicaltrials.gov. Unique identifier: NCT 01835028.